Characterization of wet and dry deposition to the nitrogen sensitive alpine ecosystems in the Colorado Rocky Mountains - Oldani, Kaley Michelle (Kansas State University, 2014)
The Colorado Front Range of the Rocky Mountains contains undeveloped, barren soils, yet in this environment there is strong evidence for a microbial role in increased nitrogen (N) export. Barren soils in alpine environments are severely carbon-limited, and organic carbon (OC) is the main energy source for heterotrophic microbial activity and sustenance of life. Atmospheric deposition can contain high amounts of OC. Atmospheric pollutants, dust events, and biological aerosols, such as bacteria, may be important contributors to the atmospheric OC load. In this stage of the research we evaluated seasonal trends and annual loadings in the chemical composition and optical spectroscopic (fluorescence and UV-vis absorbance) signatures of wet deposition and dry deposition in an alpine environment, at Niwot Ridge in the Rocky Mountains of Colorado to better understand the sources and chemical characteristics of atmospheric deposition. Dry deposition was found to be an important source of OC to the alpine. Wet deposition contributed substantially greater amounts of dissolved ammonium, nitrate, and sulfate. There were also positive relationships between dissolved organic carbon (DOC) concentrations and ammonium, nitrate and sulfate concentrations in wet deposition, which may be derived from such sources as dust and urban air pollution. We also observed the presence of seasonally-variable fluorescent components in atmospheric samples that are different from aquatic dissolved organic matter (DOM). Finally, the quality of atmospheric organic compounds reflects photodegradation during transport through the atmosphere. These results are relevant because atmospheric inputs of carbon and other nutrients may influence nitrification in barren, alpine soils and, ultimately, the export of nitrate from alpine watersheds.
Keywords: Atmospheric deposition; Nitrogen sensitive ecosystem; Alpine ecosystem; Rocky Mountains; Atmospheric Sciences (0725); Environmental Sciences (0768); Water Resource Management (0595)